Strategic exit interviewing: encouraging voice, enhancing alignment and examining process. Issue 1 (13th March 2017) - Pace, Victoria L.; Kisamore, Jennifer L.
Abstract : Purpose: To maximize their effectiveness, exit interviews should incorporate employee voice and be aligned with other HR processes. The purpose of this paper is to describe a three-step approach to the strategic use of exit interviews. Design/methodology/approach: The current study synthesizes extant theory including that of employee voice to enhance the exit interview process. A qualitative study conducted within a large marketing research organization demonstrates how exit interviews that utilize employee voice can inform HR and organizational strategy. Findings: Application of the proposed process to the case study revealed conditions, critical incidents, and cognitive processes underlying exit decisions for employees in several job categories. Qualitative exit information is used to describe corresponding employee withdrawal paths. Practical implications: Use of the three-step exit interview process is expected to enhance HR decisions. Data gathered from the three-step process can be used by HR and organizational leaders to develop action plans as well as inform an organization's strategic decisions. Originality/value: An organizational example is presented in which insight into underlying causes of voluntary turnover are discovered through exit interviews. Exit interview information suggested interventions related to HR processes. Such targeted insights from exit interviews can greatly improve retention and enhance organizational effectiveness.